Stand Structure and Dynamics of the Naturally Managed Oak-Dominated Forests and Their Relation to Environmental Variables in Swat Hindu Kush Range of Pakistan - Ataur Rahman (11044485) (2023)
Although oak woodlands are a characteristic landscape component in the Swat Hindukush Mountain ranges, little is known about their current or historical stand population structure and regeneration dynamics related to environmental variables. Therefore, the present study assessed the stand structure, regeneration status, and relationship of oak communities with environmental variables. The study assessed 30 oak-dominated forest sites using the quadrates method, sampling 300 quadrates for evaluating the phytosociological and environmental variables. The stand structures of forests were dominated by four oak species, i.e., Quercus incana, Quercus baloot, Quercus dilatata, and Quercus semecarpifolia, distributed along with the elevation. The lower elevation stand structures were most diverse and dominated by Q. incana, having higher stand parameters, i.e., importance value index, basal area, and density. In contrast, the higher-elevation stand structures were dominated by Q. semecarpifolia, having stand parameters in moderate measures, while those at intermediate elevations have lower stand parameters. The environmental variables were negatively correlated with the stand structures, i.e., elevation (r = −0.51), precipitation (r = −0.47), and relative humidity (r = −0.77), whereas soil nutrients such as Potassium concentration have a significant negative relation with stands structure (r = −0.66) indicating their vital role in sustaining the oak communities. The communities were fairly regenerated, with an age structure between 12–36 years, indicating young communities. These results concluded that the observed wide range of variability in stand characteristics reflects the mechanisms that have shaped them. The recent anthropogenic factors, i.e., military operations and natural hazards such as the flood of 2010, have deliberately affected the communities under natural restoration. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su15054002